tìm x
a) x^2( x-3)+ 12- 4x = 0
b) (2x-1)^2 - 25 = 0
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) \(x^3\)\(-\)\(\frac{1}{4}x\)\(=\)\(0\)
\(x\left(x^2-\frac{1}{4}\right)=0\)
\(\Leftrightarrow\)\(\orbr{\begin{cases}x=0\\x^2-\frac{1}{4}=0\end{cases}}\)\(\Leftrightarrow\)\(\orbr{\begin{cases}x=0\\x^2=0,5^2\end{cases}}\)\(\Leftrightarrow\)\(\orbr{\begin{cases}x=0\\x=+-0,5\end{cases}}\)
Vậy .............................
b) \(\left(2x-1\right)^2\)\(-\)\(\left(x+3\right)^2\)\(=\)\(0\)
\(\left(2x-1+x+3\right)\left(2x-1-x-3\right)=0\)
\(\left(3x+2\right)\left(x-4\right)=0\)
\(\Leftrightarrow\)\(\orbr{\begin{cases}3x+2=0\\x-4=0\end{cases}}\)\(\Leftrightarrow\)\(\orbr{\begin{cases}3x=-2\\x=4\end{cases}}\)\(\orbr{\begin{cases}x=\frac{-2}{3}\\x=4\end{cases}}\)
Vậy ................................
c) \(x^2\)\(\left(x-3\right)\)\(+\)\(12\)\(-\)\(4x\)\(=\)\(0\)
\(x^2\)\(\left(x-3\right)\)\(-\)\(4\)\(\left(x-3\right)\)\(=\)\(0\)
\(\left(x^2-4\right)\left(x-3\right)\)
\(\Leftrightarrow\)\(\orbr{\begin{cases}x^2\\x-3=0\end{cases}-4=0}\)\(\Leftrightarrow\)\(\orbr{\begin{cases}x^2\\x=3\end{cases}=2^2}\)\(\Leftrightarrow\)\(\orbr{\begin{cases}x=+-2\\x=3\end{cases}}\)
a)\(x^3-\frac{1}{4}x=0\)
\(\Leftrightarrow x\left(x^2-\frac{1}{4}\right)=0\)
\(\Leftrightarrow x\left(x-\frac{1}{2}\right)\left(x+\frac{1}{2}\right)=0\)
\(\Leftrightarrow\hept{\begin{cases}x=0\\x-\frac{1}{2}=0\\x+\frac{1}{2}=0\end{cases}\Leftrightarrow\hept{\begin{cases}x=0\\x=\frac{1}{2}\\x=-\frac{1}{2}\end{cases}}}\)
\(x^2+4x+3=0\)
\(x^2+x+3x+3=0\)
\(x\left(x+1\right)+3\left(x+1\right)=0\)
\(\left(x+1\right)\left(x+3\right)=0\)
\(\left[\begin{array}{nghiempt}x+1=0\\x+3=0\end{array}\right.\)
\(\left[\begin{array}{nghiempt}x=-1\\x=-3\end{array}\right.\)
\(4x^2+4x-3=0\)
\(4x^2-2x+6x-3=0\)
\(2x\left(2x-1\right)+3\left(2x-1\right)=0\)
\(\left(2x-1\right)\left(2x+3\right)=0\)
\(\left[\begin{array}{nghiempt}2x-1=0\\2x+3=0\end{array}\right.\)
\(\left[\begin{array}{nghiempt}2x=1\\2x=-3\end{array}\right.\)
\(\left[\begin{array}{nghiempt}x=\frac{1}{2}\\x=-\frac{3}{2}\end{array}\right.\)
\(x^2-x-12=0\)
\(x^2-4x+3x-12=0\)
\(x\left(x-4\right)+3\left(x-4\right)=0\)
\(\left(x-4\right)\left(x+3\right)=0\)
\(\left[\begin{array}{nghiempt}x-4=0\\x+3=0\end{array}\right.\)
\(\left[\begin{array}{nghiempt}x=4\\x=-3\end{array}\right.\)
\(x^2-25-\left(x-5\right)=0\)
\(\left(x-5\right)\left(x+5\right)-\left(x-5\right)=0\)
\(\left(x-5\right)\left(x+5-1\right)=0\)
\(\left(x-5\right)\left(x+4\right)=0\)
\(\left[\begin{array}{nghiempt}x-5=0\\x+4=0\end{array}\right.\)
\(\left[\begin{array}{nghiempt}x=5\\x=-4\end{array}\right.\)
\(x^2\left(x^2+1\right)-x^2-1=0\)
\(x^2\left(x^2+1\right)-\left(x^2+1\right)=0\)
\(\left(x^2+1\right)\left(x^2-1\right)=0\)
\(\left(x^2+1\right)\left(x-1\right)\left(x+1\right)=0\)
\(\left[\begin{array}{nghiempt}x-1=0\\x+1=0\end{array}\right.\) (vì \(x^2+1\ge1>0\))
\(\left[\begin{array}{nghiempt}x=1\\x=-1\end{array}\right.\)
`2(x-3)-4x=0`
`<=> 2x-6-4x=0`
`<=> -2x-6=0`
`<=>-2x=6`
`<=>x=-3`
__
`x^2-2x+1=25`
`<=>(x-1)^2=25`
`<=> (x-1)^2 = (+- 5)^2`
\(\Leftrightarrow\left[{}\begin{matrix}x-1=5\\x-1=-5\end{matrix}\right.\\ \Leftrightarrow\left[{}\begin{matrix}x=6\\x=-4\end{matrix}\right.\)
a: 2(x-3)-4x=0
=>2x-6-4x=0
=>-2x-6=0
=>2x+6=0
=>2x=-6
=>x=-3
b: \(x^2-2x+1=25\)
=>\(\left(x-1\right)^2=25\)
=>\(\left[{}\begin{matrix}x-1=5\\x-1=-5\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=6\\x=-4\end{matrix}\right.\)
`Answer:`
Bài 1:
a) \(7+2x=22-3x\)
\(\Leftrightarrow2x+3x=22-7\)
\(\Leftrightarrow5x=15\)
\(\Leftrightarrow x=3\)
b) \(8x-3=5x+12\)
\(\Leftrightarrow8x-5x=12+3\)
\(\Leftrightarrow3x=15\)
\(\Leftrightarrow x=5\)
c) \(x-12+4x=25+2x-1\)
\(\Leftrightarrow x-12+4x-25-2x+1=0\)
\(\Leftrightarrow\left(x+4x-2x\right)+\left(1-12-25\right)=0\)
\(\Leftrightarrow3x-36=0\)
\(\Leftrightarrow x=12\)
d) \(x+2x+3x-19=3x+5\)
\(\Leftrightarrow6x-19=3x+5\)
\(\Leftrightarrow6x-3x=5+19\)
\(\Leftrightarrow3x=24\)
\(\Leftrightarrow x=8\)
Bài 2:
a) \(\left(2,3x-6,9\right)\left(0,1x+2\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}2,3x-6,9=0\\0,1x+2=0\end{cases}\Leftrightarrow\orbr{\begin{cases}x=3\\x=-20\end{cases}}}\)
b) \(\left(2x+7\right)\left(x-5\right)\left(5x+1\right)=0\)
\(\Leftrightarrow2x+7=0\text{ hoặc }x-5=0\text{ hoặc }5x+1=0\)
\(\Leftrightarrow x=-\frac{7}{2}\text{ hoặc }x=5\text{ hoặc }x=-\frac{1}{5}\)
c) \(\left(4x+2\right)\left(x^2+1\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}4x+2=0\\x^2+1=0\end{cases}\Leftrightarrow\orbr{\begin{cases}x=-\frac{1}{2}\\x^2=-1\text{(Loại)}\end{cases}}}\)
d) \(\left(x^2-4\right)+\left(x-2\right)\left(3-2x\right)=0\)
\(\Leftrightarrow x^2-4+\left(3x-2x^2-6+4x\right)=0\)
\(\Leftrightarrow x^2-4=\left(-2x^2+7x-6\right)=0\)
\(\Leftrightarrow x^2-4-2x^2+7x-6=0\)
\(\Leftrightarrow-x^2+7x-10=0\)
\(\Leftrightarrow x^2-5x-2x+10=0\)
\(\Leftrightarrow x.\left(x-5\right)-2.\left(x-5\right)=0\)
\(\Leftrightarrow\left(x-5\right).\left(x-2\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}x-5=0\\x-2=0\end{cases}\Leftrightarrow\orbr{\begin{cases}x=5\\x=2\end{cases}}}\)
a) \(...\left(x+3\right)^3=5^3\Rightarrow x+3=5\Rightarrow x=2\)
b) \(...\Rightarrow-4< x< 9\)
c) \(...\Rightarrow2x+12>0\Rightarrow2x>-12\Rightarrow x>-6\)
a: =>25-4x=1
=>4x=24
hay x=6
b: =>2x-4=0
hay x=2
c: =>x-35=115
hay x=150
d: =>x-2=12
hay x=14
e: =>x-36=216
hay x=252
a) (x - 3)2 - 5.(x - 2) + 5 = 0.
<=> x^2 - 6x + 9 - 5x + 10 + 5 = 0
<=> x^2 - 11x + 24 = 0
<=> (x-3)(x-8)=0
<=> x = 3 hoặc x = 8
a) \(\left(x+3\right)^2-\left(x-2\right)^3=\left(x+5\right)\left(x^2-5x+25\right)-108\)
\(\Leftrightarrow x^2+6x+9-x^2+4x-4=x^3-5x^2+25x+5x^2-25x+125-108\)
\(\Leftrightarrow x^3-10x+12=0\Leftrightarrow\left(x-2\right)\left(x^2+2x+6\right)=0\)
\(\Leftrightarrow x=2\)( do \(x^2+2x+6=\left(x+1\right)^2+4\ge4>0\))
\(x^2\left(x-3\right)+12-4x=0\)
\(\Rightarrow x^2\left(x-3\right)-4\left(x-3\right)=0\)
\(\Rightarrow\left(x^2-4\right)\left(x-3\right)=0\)
\(\Rightarrow\left[{}\begin{matrix}x^2-4=0\\x-3=0\end{matrix}\right.\)
\(\Rightarrow\left[{}\begin{matrix}x^2=4\\x=3\end{matrix}\right.\)
\(\Rightarrow\left[{}\begin{matrix}x=3\\\left[{}\begin{matrix}x=2\\x=-2\end{matrix}\right.\end{matrix}\right.\)
\(\left(2x-1\right)^2-25=0\)
\(\Rightarrow\left(2x-1+5\right)\left(2x-1-5\right)=0\)
\(\Rightarrow\left(2x+4\right)\left(2x-6\right)=0\)
\(\Rightarrow\left[{}\begin{matrix}2x+4=0\\2x-6=0\end{matrix}\right.\)
\(\Rightarrow\left[{}\begin{matrix}2x=-4\\2x=6\end{matrix}\right.\)
\(\Rightarrow\left[{}\begin{matrix}x=-2\\x=3\end{matrix}\right.\)